Cultural Antecedents of Sustainability and Regional Economic Development - A Study of SME 'Mittelstand' Firms in Baden-Württemberg (Germany). Issue 7 (7th August 2020) - Kraus, Patrick; Stokes, Peter; Cooper, Sir Cary; Liu, Yipeng; Moore, Neil; Britzelmaier, Bernd; Tarba, Shlomo
ABSTRACT: This paper examines behavioural and regional/geographic cultural antecedents of sustainability in SME contexts. The study identifies prevailing macro-representations of sustainability in the literature and highlights an over-focus on large firms constituting the predominant unit of analysis. Moreover, there is a propensity in the literature to view sustainability primarily in terms of 'environmental' – closely linked to a corporate strategic imperative narrative of economic competitiveness and profitability. Overall, this perspective tends to generate accounts which are acultural, apolitical and ahistorical in terms of innovative actions and sustainability practices. In response, using a conceptual framework of moral identity, the paper develops a more micro-foundational insight to sustainability (developing notions of 'tangible' and 'intangible') and examines regional economic development attitudes at individual owner-manager/managing director level in small-to-medium-sized firms. Methodologically, an inductively framed interview schedule was employed with owner-managers and managing directors (n = 30) of manufacturing SMEs in the Baden-Württemberg region (Germany). The study identified a range of micro-foundational behavioural antecedents operating in the sample companies. In particular, it underlined that many of the SME owner-managers/managing directors expressed views informed by a particular moral identity connected with a perspective rooted in regionally bound, longstanding and 'expected' behaviours of trust, fairness, honesty and community responsibility.